2018
DOI: 10.1016/j.apsusc.2018.02.074
|View full text |Cite
|
Sign up to set email alerts
|

Stability of boron-doped graphene/copper interface: DFT, XPS and OSEE studies

Abstract: Two different types of boron-doped graphene/copper interfaces synthesized using two different flow rates of Ar through the bubbler containing the boron source were studied. X-ray photoelectron spectra (XPS) and optically stimulated electron emission (OSEE) measurements have demonstrated that boron-doped graphene coating provides a high corrosion resistivity ofCu-substrate with the light traces of the oxidation of carbon cover. The density functional theory calculations suggest that for the case of substituti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…In general, different parameters in CVD can be optimized for tunable growth. [123] Romani et al used a single liquid precursor (isopropyl borate) and cracked it to grow B-doped graphene by the CVD route. At the optimal growth temperature (1000 °C), pressure (75 mTorr), and growth duration (5 min), single layer B-doped graphene can be achieved, and the presence of doping was shown by XPS and Raman analyses.…”
Section: Boron-doped Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…In general, different parameters in CVD can be optimized for tunable growth. [123] Romani et al used a single liquid precursor (isopropyl borate) and cracked it to grow B-doped graphene by the CVD route. At the optimal growth temperature (1000 °C), pressure (75 mTorr), and growth duration (5 min), single layer B-doped graphene can be achieved, and the presence of doping was shown by XPS and Raman analyses.…”
Section: Boron-doped Graphenementioning
confidence: 99%
“…In general, different parameters in CVD can be optimized for tunable growth. [ 123 ] Romani et al. used a single liquid precursor (isopropyl borate) and cracked it to grow B‐doped graphene by the CVD route.…”
Section: Synthesismentioning
confidence: 99%
“…It has been proven that friction performance and service time were improved significantly when graphene was tightly bonded to the substrate . A remarkable enhancement of binding strength on a metal surface from 35 to 121 eV/atom when graphene lattice was doped by boron atoms has been reported . These results demonstrated that adding suitable impurities into graphene structure is an effective way to improve graphene adhesion on metal/metal oxide surfaces.…”
Section: Results and Discussionmentioning
confidence: 92%
“…were neither the characteristics of Cu(I) species, nor those of Cu(0), but only Cu(II) species, this implies that there was no Cu 2 O or Cu on the surface of the catalyst . Here only two peaks could be observed on samples, indicating that the oxidation state of catalysts were not pure CuO because there were no obvious shake‐up satellite peaks at about 942.8 or 962.5 eV . The peak position of XPS was affected by many factors.…”
Section: Resultsmentioning
confidence: 97%
“…[25][26][27] Here only two peaks could be observed on samples, indicating that the oxidation state of catalysts were not pure CuO because there were no obvious shake-up satellite peaks at about 942.8 or 962.5 eV. 5,28,29 The peak position of XPS was affected by many factors. After 550 ∘ C air calcination, there must be CuO species on catalysts, which were presented in the form of highly dispersed dark spots on TEM images (Fig.…”
Section: Characterization Of Cu/zsm-5 Catalystsmentioning
confidence: 99%